2015
DOI: 10.1103/physreva.91.062113
|View full text |Cite
|
Sign up to set email alerts
|

Implications and applications of the variance-based uncertainty equalities

Abstract: In quantum mechanics, the variance-based Heisenberg-type uncertainty relations are a series of mathematical inequalities posing the fundamental limits on the achievable accuracy of the state preparations. In contrast, we construct and formulate two quantum uncertainty equalities, which hold for all pairs of incompatible observables and indicate the new uncertainty relations recently introduced by L. Maccone and A. K. Pati [Phys. Rev. Lett. 113, 260401 (2014)]. Furthermore, we present an explicit interpretation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…The energy-density functional (EDF) and the generator coordinate methods (GCM) mix many mean fields with different properties (88, 89,90), whereas the other methods use simple mean fields that the states and orbitals feel. Minimization of the energy functional finds the ground states.…”
Section: General Aspects Of the Nuclear Matrix Elementsmentioning
confidence: 99%
“…The energy-density functional (EDF) and the generator coordinate methods (GCM) mix many mean fields with different properties (88, 89,90), whereas the other methods use simple mean fields that the states and orbitals feel. Minimization of the energy functional finds the ground states.…”
Section: General Aspects Of the Nuclear Matrix Elementsmentioning
confidence: 99%
“…[16], one may note that the minimum uncertainty states of such unitary operators are the ground states of the Harper Hamiltonian [22,32], which will be discussed in more detail in section V below. We have taken the ground states of the Harper Hamiltonian for dimensions 3,5,8,12, and found that our bound is not saturated for d ≥ 3. It is clear from the Table I that though the uncertainty relations are not tight, but they are tighter than that given in Ref.…”
Section: Using This In Eqmentioning
confidence: 99%
“…Recently, stronger uncertainty relations are proved which go beyond the Robertson uncertainty relations and they capture the notion of incompatible observables [4]. Uncertainty relations are at the center stage of current research in quantum theory and quantum information [5][6][7][8]. The uncertainty relations are useful from the point of view of foundational aspects and have applications in quantum technology as well [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…After these, more state-dependent [15][16][17][18][19][20] and state-independent [21][22][23][24][25][26] lower bounds of uncertainty relations were also obtained. The generalization and improvement mainly focused on the uncertainty relation capable of dealing with more than two incompatible observables, i.e., the Heisenberg-type uncertainty relation for three canonical observables [27], uncertainty relations for angular momentum [28], and arbitrary incompatible observables [17].…”
Section: Introductionmentioning
confidence: 99%